Pengembangan Majalah Biologi Materi Keselamatan Kerja di Laboratorium Biologi untuk Siswa Kelas XI Pertanian SMK Negeri 4 Muaro Jambi - Reflihadi Reflihadi (Jurnal Ilmiah Dikdaya, 2020)
This study aims to provide solutions for the problems of understanding in work safety at biology laboratory material by developing learning resources in the form of biology magazines work safety material in biology laboratory for 11th Proffesional High School On 4 Muaro Jambi. The type of this research is development research with ADDIE model. This research was conducted at kelas XI Pertanian SMK Negeri 4 Muaro Jambi. The research data was taken on January 2nd 2019 and obtained by giving a questionnaire to the media expert validator, material expert validator, a small group consisting of 6 students, a large group consisting of 19 students, a teacher of biological studies and a laboratory assistant. The results of the study show that the product is feasible to be used as learning resources. This is indicated by the results of the media validation process and the material carried out 3 times continues to increase. The percentage of stage I media validation was 60% and material validation was 61.25% in the 'not good' category, then increase in the second stage, media validation was 75% and material validation was 66.25% in the 'good' category and finally in stage III media validation was 95% and material validation was 88.75% in the 'very good' category. The results of the assessment by biology teachers with percentage of 97.5% in the 'very good' category. The results of the assessment by a laboratory assistant with percentage of 92.5% in the 'very good' category. Student trial in small groups get a percentage of 79.1% in the 'Good' category and the trials of students in large groups get a percentage of 84.8% in the 'very good' category.